Modern Approaches to Risk Management in Investment Portfolios: Strategies in Market Volatility - Loso Judijanto; Yupiter Mendrofa; Iwan Harsono; Pirmanta Sebayang; Fuadah Johari (Adisam Publisher, 2024)
Non-Indexed Publication